Adjuvant Therapy after Esophagectomy for Esophageal Cancer: Who Needs It?: Multi-institution Worldwide Observational Study - Siva Raja, MD, PhD; Thomas W. Rice, MD; Min Lu, PhD; Marie E. Semple, MPH; Andrew J. Toth, MS; Eugene H. Blackstone, MD; Sudish C. Murthy, MD, PhD; Usman Ahmad, MD; Michael McNamara, MD; Hemant Ishwaran, PhD; for the Worldwide Esophageal Cancer Collaboration Investigators (Annals of Surgery Open)
Objective:. Based on current practice guidelines, we hypothesized that most patients with esophageal cancer, particularly those with locally advanced cancer, would benefit from adjuvant therapy after esophagectomy versus esophagectomy alone. We sought to obtain a granular estimate of patient-level risk-adjusted survival for each therapeutic option by cancer histopathology and stage. Background:. Although esophagectomy alone is now an uncommon therapy for treating locally advanced esophageal cancer, the value of adjuvant therapy after esophagectomy is unknown. Methods:. From 1970 to 2014, 22,123 consecutive patients from 33 centers on 6 continents (Worldwide Esophageal Cancer Collaboration) were diagnosed with biopsy-proven adenocarcinoma (n = 7526) or squamous cell carcinoma (n = 5625), of whom 10,873 received esophagectomy alone and 2278 additional adjuvant therapy. Random forests for survival and virtual-twin analyses were performed for all-cause mortality. Results:. For adenocarcinoma, adjuvant therapy was beneficial only in pT4NanyM0 cancers (6–8 month survival benefit) and in pTanyN3M0 cancers (4–8 month benefit); a survival decrement was observed in pT1-3N0M0 cancers, with no effect on TanyN1-2M0 cancers. In squamous cell carcinoma, there was a 4 to 21 month survival benefit for pT3-4N0M0 cancers and a 4 to 15 month survival benefit for pT2-4N1-3M0 cancers. Conclusions:. Adjuvant therapy after esophagectomy appears to benefit most patients with node-positive squamous cell carcinoma, but for adenocarcinoma, its value is limited to deep cancers and to those with substantial nodal burden. Future studies of the role of adjuvant therapies should treat these 2 cancers differently, with guidelines reflecting the histopathologic-appropriate survival value of adjuvant therapy.